Optimización en la calidad de los servicios de los clientes de la Caja Trujillo, ciudad de Huamachuco, periodo 2015 - 2018 - Vargas Quiroz, Mayra Giovanna (2019)
The next job of professional sufficiency, aims to propose strategies to optimize the quality of service in the Municipal Savings and Credit Fund of Trujillo, Huamachuco agency; the main problem that was detected was that in the agency of Huamachuco, there is a quality problem, which is below the average standardized by the corporation of Caja Trujillo towards its agencies and has certain complications since it does not have enough personnel to the attention of the public which generates delay in the attention and the client feels dissatisfied. Due to this fact, there is what generates a recession in the recruitment of satisfied customers. In order to have a better panorama, the level of quality of service in customer service was measured, where the service provided by the Trujillo Box is regular, placing it at a regular quality level. Strategies proposals were made to improve the quality of service in the Trujillo Box.